Character of Gluteal Region Morphology in Young Chinese Females. (December 2018) - Cao, Saisai; Peng, Zhe; Bi, Ye; Liu, Yan; Yang, Kai; Li, Guangxue; Tang, Hui; Zang, Huiran; Qian, Youlei; Liu, Xiangyu; Song, Ping; Pu, Lee L.Q.; et al.
Abstract : Background: The female gluteal morphology is an important secondary sexual characteristic and helps accentuate and define the female body shape. Despite the increasing prevalence of gluteal augmentations in our country, little data exist regarding the morphology of the gluteal region in young Chinese females. This study analyzed a convenience sample of Chinese females and their gluteal region. Methods: Data, measurements, and photos of the following parameters were taken: age, weight, height, and body mass index (BMI). Morphology was classified into four types: A shape, V shape, round shape, and square shape. Aesthetic characteristics of each buttock were recorded. Height, weight, BMI, and gluteal projection ratio differences in different shape groups were analyzed. Results: The study sample consisted of 103 women, with ages from 23 to 27 years. The V-shaped buttock was not found in this sample. The A shape, square shape, and round shape occupied 55.3%, 38.8%, and 5.8% accordingly. Short infragluteal fold, supragluteal fossettes, lateral depression, and V-shaped crease appeared in 42.7%, 14.6%, 11.7%, and 2.9% of samples, respectively. Of the 103 samples, 39 (37.9%) fulfilled the aesthetic gluteal projection(ratio ≥ 2). The average BMI was statistically significant between each gluteal shape ( P = 0.009). Height, weight, and gluteal projection ratio showed no significant difference with the buttock shapes. Conclusions: We are the first to describe gluteal morphology in young Chinese woman using gluteal anthropometrics. The findings of the study may provide a guideline for plastic surgeons who perform gluteal augmentation in Asian patients.